Shear Flow Induced Alignment of Carbon Nanotubes in Natural Rubber - Yan He; Zhifang Cao; Lianxiang Ma (International Journal of Polymer Science)
A new procedure for the fabrication of natural rubber composite with aligned carbon nanotubes is provided in this study. The two-step approach is based on (i) the preparation of mixture latex of natural rubber, multiwalled carbon nanotubes, and other components and (ii) the orientation of carbon nanotubes by a flow field. Rubber composite sheets filled with variable volume fraction of aligned carbon nanotubes were fabricated and then confirmed by transmission electron microscopy and Raman spectroscopy studies. An obvious increase in thermal conductivity has been obtained after the alignment of carbon nanotubes. The dynamic mechanical analysis was carried out in a tear mode for the composite.